Clinico-epidemiological and pathological profile of lung cancer: a hospital based observational study in Western part of Rajasthan, India - Choudhary, C. R.; Yogi, Suresh Kumar; Purohit, Gopal; Borana, Hemant; Desai, Govind; Sharma, Satish Chandra (International Journal of Advances in Medicine, 2020)
Background: Lung cancer is the most common cancer causing deaths in men and women world-wide, responsible for over 1 million deaths annually. Although, advances in surgical techniques and combined therapies lung cancer remains a disease with a poor prognosis. Aim of the study was to evaluate the clinico-epidemiological and pathological profile in diagnosed case of lung cancer patients, presenting in the K N Chest hospital. Methods: Initial evaluation after obtaining informed consent, demography, history, clinicoradiological findings of patients and relevant investigations was recorded. Histopathological reports reviewed. Results: Our study included 108 patients with confirmed cases of lung cancer.The mean age of the patients was 57.50 years. The male: female ratio was 5.8:1. Cough was the most common presenting symptom (77.78%) followed by chest pain (62.33%). Clubbing was most commonly associated with squamous cell carcinoma. Most common radiological presentation was consolidation (42.59%) followed by mass lesion (30.55%). Most common histopathological type of lung cancer found in this study was squamous cell carcinoma 47(43.52%) followed by adenocarcinoma 42 (38.89%). Small cell carcinoma was present in 15 (13.89%) and large cell carcinoma was present in 4 (3.70%) study group. The most common pathological cell type in silica dust exposed patient in this study was squamous cell carcinoma followed by adenocarcinoma with occupational history of > 10 years of silica dust exposure in stone mines. Conclusions: Squamous cell carcinoma still remains the commonest histological subtype followed by adenocarcinoma.